Food Waste Reduction in Europe: Multi-Stakeholder Partnerships Lessons for the Global South. - ANJARASOA, Dimbilalaina Faniry (International Journal of Environmental, Sustainability, and Social Science, 2024)
Food waste is a critical global issue with significant environmental, economic, and social consequences. This paper investigates the efficacy of multi-stakeholder partnerships in addressing food waste, with a specific focus on lessons learned from initiatives taken in Europe for application in the Global South. This study uses qualitative research methods, that involves review of existing literatures and a case study analysis of the initiatives taken by the International Food Waste Coalition (IFWC). This study evaluates the impact of multi-stakeholder partnerships in food waste reduction efforts. Key themes such as collaboration, measurement, innovation, and policy advocacy emerge as critical factors in multi-stakeholder partnerships’ effectiveness. By examining the strategies and outcomes of the IFWC, this paper provides insights and recommendations applicable to regions facing similar challenges. The findings contribute to ongoing discussions on food waste management and sustainable development, emphasizing the pivotal role of multi-stakeholder partnerships in promoting collaboration between different stakeholders from different sectors all around the world and driving meaningful change on a global scale.